Exploring factors associated with workers' safety rule violations in the Chinese construction industry: a multimethod investigation - Wang, Dandan (2013)
The Chinese construction industry is China's third biggest industrial killer. Accidents causation analysis revealed that more than 80% of accidents are caused by unsafe human behaviour. The current research was focused on exploring and examining the factors affecting safety rule violations among Chinese construction workers through four main studies in which a combination of qualitative and quantitative methodologies were used. In the first study, on-site observation and organisational document analysis were conducted in fourteen construction companies to familiarise the author with the research settings and to obtain triangulation evidence for the following studies. It was followed by the second study in which interviews and focus groups were conducted among 97 managers, safety officers and workers in order to explore the factors associated with workers' rule violation. Thematic analysis revealed four main categories of factors, i.e., individual factors, managerial factors, sectoral and labour market factors, and national and cultural factors. The qualitative study was followed by questionnaire surveys (n = 700) to test in a larger management sample the qualitative study's results. Survey results complemented the qualitative study's findings. Based on the obtained results, a fourth study using the Delphi method and the modified G1 method was conducted among 17 experts in order to calculate the importance levels of each factor in influencing workers' rule violation. Although managerial factor was ranked as the most influential factor compared with other categories, some extra-organisational factors and situations were ranked at high positions amongst 24 specific factors. The results suggested that workers' behaviour need to be scrutinised not only within the context of organisational safety management, but also from the particular background and characteristics of Chinese migrant workers, Chinese construction sector, as well as the society and the culture.